2012
DOI: 10.26719/2012.18.9.935
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, perceptions and practices towards medical ethics among physician residents of University of Alexandria hospitals, Egypt

Abstract: This cross-sectional study was conducted to assess the knowledge, perceptions and practices towards medical ethics of physician residents at university hospitals in Alexandria, Egypt. A self-administered structured questionnaire was used for knowledge and perceptions and a checklist for observations of doctor -patient interactions in the outpatient setting. Only 18.0% of the 128 participating residents had obtained their knowledge from their medical education and 29.9% were dissatisfied with the roles played b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 25 publications
12
26
1
Order By: Relevance
“…Overall, only 45.1% of study participants had positive attitude towards professional ethics which is nearly similar with study in Ambo and Gondar towns which accounts 48%and 49.2% respectively (37,43). The result is slightly lower than the study conducted in Egypt which is 60% (16). The inconsistency with study in Egypt might be due to difference in study setting and study subjects.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Overall, only 45.1% of study participants had positive attitude towards professional ethics which is nearly similar with study in Ambo and Gondar towns which accounts 48%and 49.2% respectively (37,43). The result is slightly lower than the study conducted in Egypt which is 60% (16). The inconsistency with study in Egypt might be due to difference in study setting and study subjects.…”
Section: Discussionsupporting
confidence: 52%
“…In relating to knowledge, in this study, about 77% of participants reported that they can't de ne professional ethics properly. In the contrary, about 86.7% Egyptian health professionals were able to de ne it which is very high (16). The discrepancy might be due to difference in study setting and study subjects.…”
Section: Discussionmentioning
confidence: 90%
“…In our study majority 73% of students agreed that patient should always be informed of wrong doing by anyone involved in his/her treatment which is similar to study by Angadi et al 78% but lesser compared to study by Mohammed et al 83%. 4,5 This difference could be due to study conducted by Mohammed et al was among practicing physicians. 5 Study conducted in Cochin reported 80% of medical postgraduates agreed for the same.…”
Section: Discussionmentioning
confidence: 98%
“…4,5 This difference could be due to study conducted by Mohammed et al was among practicing physicians. 5 Study conducted in Cochin reported 80% of medical postgraduates agreed for the same. 5,6 In study conducted in Manipur only 32% of doctors agreed that patient should always be informed about wrong doing by doctors.…”
Section: Discussionmentioning
confidence: 98%
“…Whilst the teaching of ethics has improved markedly over the past few decades, more work is needed to ensure that ethics is taught and assessed well [1]. The fear amongst our patients is that the ethical behaviour of medical staff can be sub optimal [2]. There is a deep desire to improve and Wenger et al have demonstrated that knowledge of medical ethics can be enhanced amongst orthopaedic surgery residents with the implementation of an appropriate curriculum.…”
mentioning
confidence: 99%